Crystallization and Applications 2022
DOI: 10.5772/intechopen.94121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Parameters and Foreign Ions on the Crystal Growth of Calcium Carbonate during Scale Formation: An Overview

Abstract: Due to the insufficiency of freshwater resources and to supply the drinking water populations, many desalination processes such as reverse osmosis, electrodialysis and distillation are widely used. However, these processes are of large-scale consumers of energy and confronted with various problems such as corrosion and scale formation. In most cases, scales are made of calcium carbonate CaCO3. In the present chapter, an overview on the effect of operating parameters such as temperature, pH and supersaturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 110 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Studies on the impact of iron on the crystallization of CaCO 3 have immediate economic importance, as the CaCO 3 scale can occlude pipes in water treatment systems, desalination plants, mineral, and crude oil pipelines, among others. Contrary to the above suggestion (easy replacement of Ca by Fe ions), experimental studies [36] have shown that, in an aqueous phase and the presence of minute amounts of ferrous iron Fe +2 , calcite will not occur at all or only marginally. The calcite phase is the most stable form of crystalline calcium carbonate, which is very difficult to dissolve as soon as it nucleates and grows on the walls of pipelines.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Studies on the impact of iron on the crystallization of CaCO 3 have immediate economic importance, as the CaCO 3 scale can occlude pipes in water treatment systems, desalination plants, mineral, and crude oil pipelines, among others. Contrary to the above suggestion (easy replacement of Ca by Fe ions), experimental studies [36] have shown that, in an aqueous phase and the presence of minute amounts of ferrous iron Fe +2 , calcite will not occur at all or only marginally. The calcite phase is the most stable form of crystalline calcium carbonate, which is very difficult to dissolve as soon as it nucleates and grows on the walls of pipelines.…”
Section: Discussionmentioning
confidence: 70%
“…However, the presence of ferrous ions does not prevent the nucleation and growth of aragonite. The reason for this behavior is not yet clearly understood but has been observed ever since the problem caught the attention of scientists [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the above suggestion (easy replacement of Ca by Fe ions) many experimental studies [37] agreed that, in an aqueous phase, and in the presence of minute amounts of ferrous iron Fe +2 calcite will not occur at all or only marginally. Calcite phase is the most stable form of crystalline calcium carbonate and very difficult to dissolve as soon as it nucleates and grows at the walls of pipelines.…”
Section: Discussionmentioning
confidence: 89%
“…Studies on the interference of iron on the crystallization of CaCO3 has immediate economic importance as the scales of CaCO 3 occludes pipes in water treatment systems, desalination plants, mineral, and crude oil pipelines, etc. Contrary to the above suggestion (easy replacement of Ca by Fe ions) many experimental studies [37] agreed that, in an aqueous phase, and in the presence of minute amounts of ferrous iron Fe +2 calcite will not occur at all or only marginally. Calcite phase is the most stable form of crystalline calcium carbonate and very difficult to dissolve as soon as it nucleates and grows at the walls of pipelines.…”
mentioning
confidence: 78%
See 1 more Smart Citation